2019
DOI: 10.2147/cmar.s213264
|View full text |Cite
|
Sign up to set email alerts
|

<p>Neutrophil-to-lymphocyte ratio predicts the prognosis of stage II nasopharyngeal carcinoma</p>

Abstract: PurposeTo assess the prognostic value of the neutrophil-to-lymphocyte ratio (NLR) in stage II nasopharyngeal carcinoma (NPC).MethodsStage II (2010 UICC/AJCC staging system) NPC patients treated between January 2007 and December 2014 were retrospectively analyzed. The NLR was calculated from peripheral blood cell counts before treatment. The optimal cut-off value of NLR was determined by receiver operating characteristic curve analysis. Survival rates were compared according to the NLR value. Multivariable Cox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…An increased NLR or MLR before treatment is a poor prognostic factor for different cancers, including gastrointestinal cancers, soft tissue sarcomas, nasopharyngeal carcinoma, and lung cancer. [16][17][18][19] In our study, patients with low NLR and MLR values (NLR <2.85 and MLR <.30) had longer PFS and OS. The relative proportion of neutrophils is larger in patients with a high NLR and they tend to have worse prognosis.…”
Section: Discussionsupporting
confidence: 47%
“…An increased NLR or MLR before treatment is a poor prognostic factor for different cancers, including gastrointestinal cancers, soft tissue sarcomas, nasopharyngeal carcinoma, and lung cancer. [16][17][18][19] In our study, patients with low NLR and MLR values (NLR <2.85 and MLR <.30) had longer PFS and OS. The relative proportion of neutrophils is larger in patients with a high NLR and they tend to have worse prognosis.…”
Section: Discussionsupporting
confidence: 47%
“…The prognostic value of NLR, PLR, and SII has been reported in many types of cancers, including NPC. Pan et al ( 27 ) conducted a retrospective study in stage II NPC patients and found that NLR was an independent prognostic biomarker in stage II NPC patients; NLR≥2.92 was associated with poorer 5-year OS (84.3% vs. 97.4%, p =0.001). Another study in NPC patients without distant metastasis reported that NLR≥ 2.28 and PLR≥174 were significantly associated with a shorter OS ( p <0.05), and NLR≥2.28 was associated with a shorter PFS ( p <0.05) ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…3 Following the initial report of peripheral immune alteration in patients with malignant tumors in the 1960s, 4 the predictive effects of immune-related serum biomarkers on the progression, therapy, and prognosis of cancer have garnered attention. 5,6 While some studies have investigated the relationship between peripheral immune-related biomarkers and outcome in patients with NPC, 7,8 they have focused mainly toward a unidirectional NPC progression effect using Kaplan-Meier survival curves. To date, however, no research has clearly simulated a precise and integrated restricted spline curve that represents the relationship between immune-related indices and NPC.…”
Section: Introductionmentioning
confidence: 99%